A psychosocial intervention for stroke survivors and carers: 12–month outcomes of a randomized controlled trial. Issue 8 (16th November 2020) - Minshall, Catherine; Castle, David J.; Thompson, David R.; Pascoe, Michaela; Cameron, Jan; McCabe, Marita; Apputhurai, Pragalathan; Knowles, Simon R.; Jenkins, Zoe; Ski, Chantal F.
ABSTRACT: Background and Purpose : Stroke can have a devastating impact on the mental and physical health of stroke survivors and their carers. We aimed to evaluate the effectiveness of a novel psychosocial intervention designed to improve health outcomes in both groups. Methods : We conducted a randomized controlled trial of a personalized psychosocial intervention (eight 1-hour weekly sessions plus one booster) compared to usual care for adult stroke survivors and carers. Participants recruited from hospital services and community referrals completed questionnaires at baseline, 3, 6, and 12 months. Primary outcomes were quality of life and self-efficacy; secondary outcomes were depressive and anxiety symptoms, coping, illness perception, work and social adjustment, carer strain, and carer satisfaction. Mixed-effect model repeated measures analysis between groups and across time was conducted. Results : Of the 173 participants recruited (89 stroke survivors; 84 carers), a total of 137 participants – 73 stroke survivors (intervention n = 42; usual care n = 31) and 64 carers (intervention n = 35; usual care n = 29) – underwent analysis up to 12 months. No statistically significant differences were found in the primary outcomes between groups over time, though a significant improvement in carer satisfaction was found at 6 months in the intervention group compared to the usual care group. Conclusion : A personalized psychosocial intervention resulted in a significant improvement in carer satisfaction at 6 months but in no other outcomes. A lack of available services and barriers to social engagement may have impeded the effectiveness of this intervention.